Acute Effects of Different Blood Flow Restriction Protocols on Bar Velocity During the Squat Exercise - Wilk, Michal; Trybulski, Robert; Krzysztofik, Michal; Wojdala, Grzegorz; Campos, Yuri; Zajac, Adam; Lulińska, Ewelina; Stastny, Petr (Frontiers in Physiology, 2021)
The main goal of the present study was to evaluate the effects of different blood flow restriction (BFR) protocols (continuous and intermittent) on peak bar velocity (PV) and mean bar velocity (MV) during the squat exercise at progressive loads, from 40 to 90% 1RM. Eleven healthy men (age = 23.4 ± 3.1 years; body mass = 88.5 ± 12.1 kg; squat 1RM = 183.2 ± 30.7 kg; resistance training experience, 5.7 ± 3.6 years) performed experimental sessions once a week for 3 weeks in random and counterbalanced order: without BFR (NO-BFR), with intermittent BFR (I-BFR), and with continuous BFR (C-BFR). During the experimental session, the participants performed six sets of the barbell squat exercise with loads from 40 to 90% 1RM. In each set, they performed two repetitions. During the C-BFR session, the cuffs were maintained throughout the training session. During the I-BFR, the cuffs were used only during the exercise and released for each rest interval. The BFR pressure was set to ∼80% arterial occlusion pressure (AOP). Analyses of variance showed a statistically significant interaction for MV (p < 0.02; η2 = 0.18). However, the post hoc analysis did not show significant differences between particular conditions for particular loads. There was no significant condition × load interaction for PV (p = 0.16; η2 = 0.13). Furthermore, there were no main effects for conditions in MV (p = 0.38; η2 = 0.09) as well as in PV (p = 0.94; η2 = 0.01). The results indicate that the different BFR protocols used during lower body resistance exercises did not reduce peak bar velocity and mean bar velocity during the squat exercise performed with various loads.